2000
DOI: 10.1007/bf03343763
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that Ghrelin, the natural GH secretagogue (GHS)-receptor ligand, strongly stimulates GH secretion in humans

Abstract: An endogenous ligand for the GH secretagogue-receptor (GHS-R) has been recently purified from rat and human stomach and named Ghrelin. It has been demonstrated that Ghrelin specifically stimulates GH secretion from rat pituitary cells in culture as well as in rats in vivo. In this preliminary study, in 4 normal adults [age (mean+/-SE): 28.6+/-3.5 yr; body mass index (BMI): 22.3+/-2.1 kg/m2] we administered 1.0 microg/kg Ghrelin or GHRH-29 to compare their GH-releasing activities in humans. In all subjects Ghre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
201
0
14

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(222 citation statements)
references
References 9 publications
7
201
0
14
Order By: Relevance
“…6.79x10 6 copy number/µg total RNA in normal tissue vs 1.41x10 7 in malignant tissue, p=not significant.…”
Section: Vegf-189mentioning
confidence: 91%
See 1 more Smart Citation
“…6.79x10 6 copy number/µg total RNA in normal tissue vs 1.41x10 7 in malignant tissue, p=not significant.…”
Section: Vegf-189mentioning
confidence: 91%
“…Ghrelin acts directly on the anterior pituitary gland to stimulate GH release, and in vivo studies in humans involving intravenous injections of ghrelin demonstrate that the GH response to ghrelin is greater than that to GHRH 7 . However, despite its potent effect on GH release, there is some doubt over the primary role for ghrelin in the regulation of GH secretion, following a report indicating that no specific phenotype was observed in a ghrelin knockout mouse 8 .…”
Section: Ghrelinmentioning
confidence: 99%
“…Ghrelin, the endogenous ligand specific for the growth hormone (GH) secretagogue receptor, was discovered in 1999 by Kojima et al 1 Besides being a strong stimulator of GH secretion, 2,3 several studies have reported ghrelin to be a potent peptide involved in appetite and food regulation, as it increases food intake and promotes adiposity in both humans and animals. [4][5][6] Reduced levels have been reported in obese subjects, 7,8 whereas increased concentrations have been found in patients with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP-1 concentrations were associated with ghrelin concentrations only in subjects with IR. Since ghrelin has a powerful GH-releasing effect in experimental settings [1,8,17,18], it has been proposed to serve as a regulator of somatotroph function together with GHRH and somatostatin [39,40]. However, the physiological role of ghrelin in the regulation of GH/IGF-I axis has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that ghrelin has a powerful, rapid, and dose-dependent effect on GH release in experimental studies [1,17,18], the functional role of ghrelin in the long-term regulation of GH concentrations in physiological conditions has not yet been clarified. The recent studies are either for [19][20][21][22] or against [23][24][25][26] the role of ghrelin in the regulation of GH concentrations.…”
mentioning
confidence: 99%